Hip Inflammatory Conditions: A Practical Differential Diagnosis Algorithmic Approach in Adults and Children - Jaremko, Jacob L.; Teh, James; Weidekamm, Claudia; Jans, Lennart; Herregods, Nele (Seminars in Musculoskeletal Radiology, 2019)
The child or adult patient presenting with acute hip pain in the absence of major trauma often presents a difficult diagnostic dilemma, due to the complex anatomy and diversity of pathology at the hip. A correct diagnosis is important because untreated hip inflammatory disease can lead to lifelong morbidity from structural damage at this weightbearing joint. An effective and efficient process of reaching an appropriate diagnosis often requires multiple imaging modalities overseen by careful clinical judgment. This article reviews an algorithmic approach to imaging the acutely painful hip, with attention to uses and limitations of each imaging modality, and it offers details on the key differential diagnoses in adults and children.
Keywords: hip; inflammation; arthritis; pediatric; adult